Modelling non-muslim consumers’ adoption of halal food in Malaysia / Ismalaili Ismail ... [et al.] - Ismail, Ismalaili; Md Sabri, Sabiroh; Abd Mutalib, Hasyeilla; Annuar, Nursyamilah (2024)
The concept of halal food is rooted in Islamic religious principles and serves as a guide for Muslims in their dietary choices. However, this concept and principles are not typically central to the lives of non-Muslims. Nevertheless, there has been a recent trend of non-Muslim consumers in Malaysia showing acceptance towards halal food, raising intriguing questions that require further exploration. Hence, this study aims to examine the factors that may impact the purchasing intentions and behaviour of non-Muslim consumers regarding halal food within the Malaysian setting. The study analyses the complex relationships between five key variables: preferences for halal food, social influence, assurance in halal food, purchase intention regarding halal products, and actual purchase behaviour. Furthermore, it investigates the potential moderating effect of government initiatives in promoting halal food adoption among non-Muslim consumers. Employing a methodical sampling approach, data was gathered via self-administered surveys from 422 non-Muslim participants in the Klang Valley region. The structural equation modelling was employed to analyse the acquired data. The findings reveal several noteworthy insights. The findings were then used to develop a model to support marketers, food producers, and policymakers in their decision-making. By understanding the drivers behind non-Muslim consumers’ adoption of halal food, stakeholders can develop more effective marketing strategies and policies to foster greater awareness and acceptance of halal products among this demographic in Malaysia.